Impedance and Mössbauer spectroscopy study of BiCu3Ti3FeO12 dielectric matrix - Freitas, Daniel Barros de (2021)
In the present work, an electroceramic of the perovskite family, BiCu3Ti3FeO12 (BCTFO), was synthesized by the solid-state reaction method. The structural study was performed by X-ray diffraction and Mössbauer and Raman spectroscopy. Electric and dielectric properties were analyzed by impedance spectroscopy and the Hakki-Coleman method. Due to the BCTFO is isostructural of the CaCu3Ti4O12 (CCTO), the BCTFO presents as a promissory electroceramic. Mössbauer spectroscopy reveals paramagnetic spectra to BCTFO, with two octahedral sites for iron ions. Regarding dielectric properties, for 1 Hz, BCTFO presents a high relative dielectric permittivity (εr ≈ 1 × 104) and dielectric loss (tan δ > 1) and εr = 230.88, tan δ ≈ 1 × 10–2 in the microwave range. The produced ceramic exhibited a high resonance frequency temperature coefficient (τf) with a value of + 2852 ppm °C−1, making it a candidate for fabrication of the thermostable electroceramic composites with other ceramic matrices with negative τf values improving the thermal stability.